theorem zltznsub0 (a b: nat): $ a -ZN b a < b $;
Step | Hyp | Ref | Expression |
1 |
|
|
(b0 a -Z b0 b <Z 0 <-> a -ZN b <Z 0) -> (b0 a -Z b0 b <Z 0 <-> a < b) -> (a -ZN b <Z 0 <-> a < b) |
2 |
|
|
b0 a -Z b0 b = a -ZN b -> (b0 a -Z b0 b <Z 0 <-> a -ZN b <Z 0) |
3 |
|
|
|
4 |
|
|
b0 a -Z b0 b <Z 0 <-> a -ZN b <Z 0 |
5 |
|
|
(b0 a -Z b0 b <Z 0 <-> a < b) -> (a -ZN b <Z 0 <-> a < b) |
6 |
|
|
(b0 a -Z b0 b <Z 0 <-> b0 a <Z b0 b) -> (b0 a <Z b0 b <-> a < b) -> (b0 a -Z b0 b <Z 0 <-> a < b) |
7 |
|
|
b0 a -Z b0 b <Z 0 <-> b0 a <Z b0 b |
8 |
|
|
(b0 a <Z b0 b <-> a < b) -> (b0 a -Z b0 b <Z 0 <-> a < b) |
9 |
|
|
|
10 |
|
|
b0 a -Z b0 b <Z 0 <-> a < b |
11 |
|
|
|
Axiom use
axs_prop_calc (+5)
(ax_1,
ax_2,
ax_3,
ax_mp,
itru),
axs_pred_calc (+8)
(ax_gen,
ax_4,
ax_5,
ax_6,
ax_7,
ax_10,
ax_11,
ax_12),
axs_set (+2)
(elab,
ax_8),
axs_the (+2)
(theid,
the0),
axs_peano (+9)
(peano1,
peano2,
peano5,
addeq,
muleq,
add0,
addS,
mul0,
mulS)